2017
DOI: 10.1007/s11629-016-4014-3
|View full text |Cite
|
Sign up to set email alerts
|

Active earth pressure acting on retaining wall considering anisotropic seepage effect

Abstract: This paper presents a general solution for active earth pressure acting on a vertical retaining wall with a drainage system along the soil-structure interface. The backfill has a horizontal surface and is composed of cohesionless and fully saturated sand with anisotropic permeability along the vertical and horizontal directions. The extremely unfavourable seepage flow on the back of the retaining wall due to heavy rainfall or other causes will dramatically increase the active earth pressure acting on the retai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…It is also observed that, for all the ases of an angle of friction corresponding to ϕ=26 0 , 30 0 , 36 0 , 40 0 and 46 0 both the active and passive earth pressure distribution result shows maximum value, at the base of the wall. A Similar trend of results was reported previously in the literature [21,23,24]. Many researchers have associated the reason for this behavior as large wall deflection in the higher elevation of the wall and restrained or a very smaller wall deflection in the bottom of the wall.…”
Section: Results and Analysissupporting
confidence: 89%
“…It is also observed that, for all the ases of an angle of friction corresponding to ϕ=26 0 , 30 0 , 36 0 , 40 0 and 46 0 both the active and passive earth pressure distribution result shows maximum value, at the base of the wall. A Similar trend of results was reported previously in the literature [21,23,24]. Many researchers have associated the reason for this behavior as large wall deflection in the higher elevation of the wall and restrained or a very smaller wall deflection in the bottom of the wall.…”
Section: Results and Analysissupporting
confidence: 89%
“…Note that these assumptions have also been adopted for the analysis of passive earth pressure acting on retaining wall, e.g., Morrison and Ebeling (1995), Soubra and Macuh (2002), and Patki et al (2015). In particular, the same boundary conditions of seepage flow inside the backfill were also adopted in Barros (2006), Wang et al (2008), Santos and Barros (2015), and Hu et al (2017). Distribution of the normalized pressure head, h p /H, along a log-spiral failure surface is illustrated in Fig.…”
Section: Applications Of the Proposed Methodsmentioning
confidence: 99%
“…To investigate the effect of the anisotropy of seepage flow, the ratio of permeability coefficient ξ=(k y /k x ) 1/2 was introduced by Hu et al (2017), and the solution to the Laplace equation for anisotropic seepage can be then obtained as…”
Section: Anisotropic Seepage Solutionsmentioning
confidence: 99%
“…Field measurements have shown that permeability values in the horizontal direction are multiples of those in the vertical direction; this can significantly affect the pore pressure distribution in the backfill behind the wall (Kenney 1963;Head 1988;Jeng et al 2001;Hazelton and Murphy 2007). By assuming that the horizontal axis coincides with the direction of the maximum permeability, Hu et al (2017) showed analytically that the anisotropic permeability of the backfill can significantly affect D r a f t the distribution of both the pore water pressure and the active earth pressure on retaining structures. However, studies of the passive earth pressure including anisotropic seepage flow are rarely considered and thus this aspect requires further investigation.…”
Section: Introductionmentioning
confidence: 99%